Pendampingan Penyusunan Laporan Keuangan BUMDes Manunggal Dadi Mulyo, Desa Kwadungan Gunung, Kecamatan Kledung, Kabupaten Temanggung: Assistance in the Preparation of Financial Reports for BUMDes Manunggal Dadi Mulyo, Kwadungan Gunung Village, Kledung District, Temanggung Regency - Rokhaniyah, Siti; Manurung, Herlina; Khotijah, Siti Afidatul; Nugraheni, Agustina Prativi; Susilo, Ghina Fitri Ariesta; Mabruri, Muhammad; Kurniawan, Ferdi Rahmat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Manunggal Dadi Mulyo Village-Owned Enterprise (BUMDes) in Kwadungan Gunung Village, Kledung District, Temanggung Regency, has been operating for six years. BUMDes plays a strategic role in rural economic development through its various business units. One of the main obstacles faced is the lack of understanding and skills of managers in preparing financial reports based on Financial Accounting Standards (FAS). Transparency and accountability in village fund management are becoming increasingly important to increase public trust, access to funding, and support business aspirations. Therefore, this mentoring is necessary to help BUMDes establish a more organized and systematic recording system that complies with applicable accounting standards. This program aims to increase the understanding of BUMDes managers about the importance of accurate and transparent financial reports. This activity was carried out in stages: problem identification, training and workshops, practice and mentoring, and monitoring and evaluation. This activity was effective in providing participants with an understanding of the concept of BUMDes financial reporting. This is evident in the significant increase in post-test scores. This activity is expected to enhance the quality of BUMDes' financial management and reporting, promoting transparency and accountability, while encouraging the development of professional, sustainable BUMDes, and contributing to the welfare of village communities.